Penggunaan Media Gambar Islami dalam Meningkatkan Kemampuan Belajar Fiqih Siswa Kelas III Madrasah Ibtidaiyah Syaichona Cholil Kutai Timur Tahun Pelajaran 2024/2025 - Mubarokah, Rifa Atil; Husain, Ahmadi (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study explores how Islamic picture media can enhance the Fiqh learning abilities of third-grade students at Madrasah Ibtidaiyah Syaichona Cholil in East Kutai during the 2024/2025 academic year. The research stems from the observation that many students struggle to grasp Fiqh material, largely because of its abstract and theoretical nature. To address this challenge, educators need learning media that align with the cognitive development of students at the elementary level. Using a descriptive qualitative approach, the study gathered data through classroom observations, interviews with Islamic Religious Education teachers and students, and documentation of teaching and learning activities. The researchers analyzed the data inductively through the stages of data reduction, data display, and conclusion drawing. The findings reveal that Islamic picture media significantly improved the delivery of Fiqh material. The visual content made abstract concepts more concrete, engaging, and easier for students to understand. Students demonstrated increased interest and enthusiasm in class, and they showed stronger recall and comprehension of key topics such as ablution (wudu), prayer (salat), and dry ablution (tayammum). Teachers also reported a more dynamic and interactive classroom environment. In conclusion, the study confirms that Islamic picture media is an effective tool for improving students’ understanding of Fiqh. It not only supports conceptual learning but also creates a more enjoyable and participatory educational experience for both students and teachers.